Synergistic effect of atorvastatin and cyanidin-3-glucoside against angiotensin II-mediated vascular smooth muscle cell proliferation and migration through MAPK and PI3K/Akt pathways - Rungusa Pantan (2018)
© 2016 The Pharmaceutical Society of Korea This study aimed to investigate the mechanism of cyanidin-3-glucoside (C3G) in synergy with atorvastatin, even when it is used in low concentrations. Human aortic smooth muscle cells (HASMCs) were used to verify the synergistic mechanism of atorvastatin and C3G against angiotensin II-induced proliferation and migration. BrdU incorporation assay was used to evaluate cell proliferation. Wound healing and Boyden chamber assays were used to investigate cell migration. The cell cycle was examined using flow cytometry. The results revealed that atorvastatin and C3G exhibit a synergistic effect in ameliorating HASMC proliferation and migration by enhancing cell cycle arrest. In addition, these effects also decreased mitogen-activated protein kinase (MAPK) activity by attenuating the expression of phospho-p38, phospho-extracellular signaling-regulated kinase 1/2, and phospho-c-Jun N-terminal kinase. Furthermore, the combination of atorvastatin and C3G modulated the PI3K/Akt pathway and upregulated p21Cip1, which was associated with decreases in cyclin D1 and phospho-retinoblastoma expressions. The synergistic effect of atorvastatin and C3G induced anti-proliferation and anti-migration through MAPK and PI3K/Akt pathways mediated by AT1R. These results suggest that the synergistic effect of atorvastatin and C3G may be an alternative therapy for atherosclerosis patients.